2014
DOI: 10.3138/ptc.2012-45bc
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Physical Loading Tasks and Knee Osteoarthritis: A Review of the Evidence

Abstract: Purpose: To perform a systematic review with best evidence synthesis examining the literature on the relationship between occupational loading tasks and knee osteoarthritis (OA). Methods: Two databases were searched to identify articles published between 1946 and April, 2011. Eligible studies were those that (1) included adults reporting on their employment history; (2) measured individuals' exposure to work-related activities with heavy loading in the knee joint; and (3) identified presence of knee OA (determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 47 publications
(201 reference statements)
1
71
0
7
Order By: Relevance
“…Yet there was no effect when squatting and kneeling were examined individually. This diversity in findings has been noted previously (7,14,27), and it highlights the need for attention to measurement, including whether compartmen talizing or differentiating among knee bending tasks accurately reflects real world work conditions in the frequency and duration of knee bending, and whether knee bending occurs in conjunction with lifting heavy loads (7,16,27). Some jurisdictions are trying to address these issues and have identified minimum thresholds for frequency and duration of kneeling related to work compensation claims (22), but in the absence of detailed evidence, thresholds are set high.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Yet there was no effect when squatting and kneeling were examined individually. This diversity in findings has been noted previously (7,14,27), and it highlights the need for attention to measurement, including whether compartmen talizing or differentiating among knee bending tasks accurately reflects real world work conditions in the frequency and duration of knee bending, and whether knee bending occurs in conjunction with lifting heavy loads (7,16,27). Some jurisdictions are trying to address these issues and have identified minimum thresholds for frequency and duration of kneeling related to work compensation claims (22), but in the absence of detailed evidence, thresholds are set high.…”
Section: Discussionsupporting
confidence: 82%
“…Several excellent reviews of the literature have examined occu pational factors and OA (6)(7)(8)(9)(10)(11)(12)(14)(15)(16)27). Most have focused on knees or hips, with less attention to other joints, differences between men and women, and dose response data.…”
Section: Introductionmentioning
confidence: 99%
“…OA is the most common joint disease in the world, with a prevalence of 10–15% of adults, and causes chronic pain and disability [2,3]. In a study in Korea, OA prevalence was 3.3% in males and 16.0% in females aged 50 years and older [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been at least 2 meta-analyses concluding that there was an association of knee OA in males with certain occupational activity exposure but this could not be demonstrated in females [13,15] In partial agreement with these findings, a more recent meta-analysis concluded that the evidence for a clear association between occupation and knee OA in males was "moderate" whereas in females there was deemed to be only "limited" evidence for a clear association [16]. Overall data from 3 meta-analyses appears to highlight some doubt over the existence of any link between female occupational activity and subsequent knee OA.…”
Section: Differences In Rates Of Occupation Related Oa In Males and Fmentioning
confidence: 90%